Relatório de Estágio Profissional "O caminho para a mudança de uma identidade" - Pedro Xavier de Sequeira Almeida (2019)
The document in question arises within the scope of the Professional Internship inserted in the 2nd year of the master's degree in Teaching Physical Education in Basic and Secondary Education. The main objective is to make known all the tasks and experiences carried out by the student-trainee, in a context of Professional Internship. Thus, this is a defining moment in the life of a teacher, it's where he as the opportunity to have the first contact with the profession. My Professional Internship was held at Rio Tinto Secondary School, with a trainee core consisting of 4 trainee students, a cooperating teacher and a tutor from my college. I organized the internship report into seven chapters, which explain everything that was experienced during this internship. Chapter number one, "Introduction," summarily summarizes what I did in the internship report. The second chapter, "Personal Framing," mentions the path taken up to this point and refers to the expectations I had on this professional stage. The third chapter, "Framework of Professional Practice", refers to the characterization of the medium / context of the Professional Internship. The fourth chapter, "Organization and Management of Teaching and Learning", is where I mirror the whole process of teaching learning that I accomplished during this school year. The fifth chapter, "Participation in school and relationship with the community," is where I talk about all the activities, I've been involved in. In the sixth chapter, "Study," I outline my action-research study on the influence of ranking on student motivation in physical education classes. It is concluded that there are more factors that influence the motivation of students in Physical Education, beyond classification. Finally, "Final conclusions and perspectives of the future", is where I make the total balance on the entire Professional Internship and what are my perspectives for the future.